2014
DOI: 10.1097/pdm.0000000000000031
|View full text |Cite
|
Sign up to set email alerts
|

Analytical Performance of a Formalin-fixed Paraffin-embedded Tissue-based 634-probe Prognostic Assay for Predicting Outcome of Patients With Stage II Colon Cancer

Abstract: A formalin-fixed paraffin-embedded tissue-based prognostic assay to assess the risk for recurrence in stage II colon cancer has recently been clinically validated. This study describes the analytical performance and quality control measures of the assay. The reportable range was determined to be [-1.129, 1.414] in risk score units. The accuracy was evaluated with a split sample comparison within the production lab and between the production lab and a reference lab. The concordance between the replicates within… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…12 Institutional review board approval and patient informed consent were required at each participating institution. The study excluded patients with high-risk features, and the overall risk of recurrence observed in the study was 14.6% at 5 years.…”
Section: Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…12 Institutional review board approval and patient informed consent were required at each participating institution. The study excluded patients with high-risk features, and the overall risk of recurrence observed in the study was 14.6% at 5 years.…”
Section: Patientsmentioning
confidence: 99%
“…6 The analytical properties of this assay have also been reported. 12 The assay was developed and intended for use on FFPE, a commonly used, standard method of tumor tissue preservation.…”
Section: Introductionmentioning
confidence: 99%